Storage of cuttings before and after grafting influences survival and vigor of vine grafts - Pertille, Rafael Henrique; Sachet, Marcos Robson; Guerrezi, Marieli Teresinha; Grigolo, Chaiane Renata; Citadin, Idemir (Revista Ceres, 2025)
Several grafting methods have been developed, and bench grafting with stratification is the most widely used technique, except in Brazil, which is still in adaptation. The objective of this study was to evaluate for how long plant material can be stored before the grafting and the optimum temperature for stratification. Cultivar ‘Paulsen 1103’ was used as rootstock and ‘Niagara Rosada’ as scion cultivar. The storage period treatments were 0, 30, 60 and 90 days at the temperature of 3 °C and 95% of relative humidity. After the storage period, the branches were removed from the cold chamber, taken to grafting, and then placed at 19 °C and 24 °C for stratification. After 21 days of stratification, the vine grafts were planted in commercial substrate and left to grow for 160 days. The vine cuttings of cultivars Niagara and Paulsen 1103 can be stored in cold chamber at 3 °C for 90 days and, during this period, bench grafting can be performed at any time. However, the vines from cuttings stored in cold chamber for more than 30 days have better growth. It is recommended to stratify the vine grafts at 19 °C.